2007
DOI: 10.1111/j.1744-6155.2007.00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Practices and Environment and the Risk of Sudden Infant Death Syndrome in Turkey

Abstract: Public health interventions should alert women to the increased risk of sudden infant death syndrome associated with identifiable risk factors, and specific intervention campaigns for safe sleeping can be developed for Turkish families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Ayrıca bebeklerin yataklarında yastık kullanılmaması önerilmektedir (24). Annelerin çoğunluğu literatürde olduğu gibi bizim çalışmamızda da bebeklerini uyuturken yastık kullanmaktadır (13,14,22). Ülkemizde sağlık çalışanlarına yapılan bir araştırmada riskli olmasına rağmen bebekler uyurken yastık kullanılabileceğini söyleyen pediatri hemşirelerin oranı %32, çocuk doktorlarının ise %23,8 olarak belirtilmiştir (25).…”
Section: Veri Toplamaunclassified
“…Ayrıca bebeklerin yataklarında yastık kullanılmaması önerilmektedir (24). Annelerin çoğunluğu literatürde olduğu gibi bizim çalışmamızda da bebeklerini uyuturken yastık kullanmaktadır (13,14,22). Ülkemizde sağlık çalışanlarına yapılan bir araştırmada riskli olmasına rağmen bebekler uyurken yastık kullanılabileceğini söyleyen pediatri hemşirelerin oranı %32, çocuk doktorlarının ise %23,8 olarak belirtilmiştir (25).…”
Section: Veri Toplamaunclassified
“…In the present study, it was found that 22.5% of the mothers covered their infants' heads or face while sleeping. In our country, the practice of covering the face of the infant, which is considered a traditional practice to protect babies from surrounding hazards, varies between 21.9% and 49.3% in different studies (12,13,15,18). In the present study, it was determined that 83.8% of the rooms where infants slept were heated by natural gas.…”
Section: Resultsmentioning
confidence: 63%
“…In the present study, it was determined that 83.8% of the rooms where infants slept were heated by natural gas. Efe et al (15) found that 74.9% of the infants resided in stove-heated houses. The American Academy of Pediatrics (AAP) recommends that for a safe sleeping environment, the room temperature not be excessively increased and that the room be ventilated (1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations